THE RELATIONSHIP OF RANGE OF MOTION AND GRIP STRENGTH OF THE HAND WITH DISEASE ACTIVITY, HAND FUNCTIONS AND DISABILITY IN PATIENTS WITH RHEUMATOID ARTHRITIS - Nurettin Taştekin,; Kaan Uzunca,; Murat Birtane,; Derya Demirbağ Kabayel,; Gülnur Öztürk, (Archives of Rheumatology, 2006)
Objective: Wrist and hand joints are the first and the most frequently involved joints in rheumatoid arthritis (RA). Hand involvement and functions are of the most important factors that determine the impact of the disease on daily living activities. The purpose of this study was to evaluate the relation of hand and wrist range of motion (ROM) and hand grip strength values with disease activity, hand function and disability. Patients and Methods: Thirty-eight patients (7 male, 31 female) who had been diagnosed as RA according to American Collage of Rheumatology (ACR) criterion were recruited to the study. The disease activity scores of all the patients were determined by using Disease activity score-28 (DAS-28). The ROM of the wrist and finger joints were measured both by using standard goniometry and finger goniometry. Palm to pinch distance was measured with a tape measure and noted in centimetres. Hand grip, key grip, palmar grip, tip grip (1st-3rd finger) strength were obtained by a pinchmeter and Jamar dynamometry. Hand functions of all patients were evaluated by Duruoz Hand Index (DHI). Disability was scored by using Health assessment questionnaire (HAQ). The relations between DAS-28, DHI and HAQ with ROM and grip strength values were analysed. Results: The average age of patients was 53.5±13.1. Average values of DAS-28, DHI, HAQ were found to be 3.5±1.6, 9.2±16.6, 0.7±0.7, consecutively. DAS-28 correlated positively with palm to pinch distance values of 2nd-5th fingers and negatively with total ROM values of 2nd-5th fingers of both hands, hand grip strength, key grip, palmar grip, tip grip strength (p<0.05). Similarly, DHI and HAQ scores correlated positively with palm to pinch distance values of 2nd-5th fingers and negatively with total ROM values of 2nd-5th fingers of both hands, hand grip strength, key grip, palmar grip, tip grip strength (p<0.05). Conclusion: Disease activity affects ROM values of hand and wrist joints and grip strength in RA. These two conditions cause a limitation in the usage of hand in daily living activities. (Rheumatism 2006; 21: 13-7)